2022
DOI: 10.1186/s42522-022-00067-w
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices associated with zoonotic disease transmission risk in North Sulawesi, Indonesia

Abstract: Background Hunters, vendors, and consumers are key actors in the wildlife trade value chain in North Sulawesi, Indonesia, and potentially face an elevated risk of exposure to zoonotic diseases. Understanding the knowledge, attitudes, and practices (KAP) associated with the risk of zoonotic disease transmission in these communities is therefore critical for developing recommendations to prevent or mitigate zoonotic outbreaks in the future. Methods Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…However, its contribution to increasing awareness and understanding of hazards remained limited for some stakeholders (2 [2-3]). Conducting Knowledge, Attitude, and Practices surveys can help identify this contribution [53]. OH surveillance led to some policy changes (2.5 [1.25-3]), such as updating shelf life for risk products and revising antimicrobial use policies in veterinary medicine and humans.…”
Section: Resultsmentioning
confidence: 99%
“…However, its contribution to increasing awareness and understanding of hazards remained limited for some stakeholders (2 [2-3]). Conducting Knowledge, Attitude, and Practices surveys can help identify this contribution [53]. OH surveillance led to some policy changes (2.5 [1.25-3]), such as updating shelf life for risk products and revising antimicrobial use policies in veterinary medicine and humans.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is similar to previous reports. For instance, Kusumaningrum et al [32] reported a low level of awareness of zoonotic diseases among communities involved in the wildlife trade value chain in Indonesia.…”
Section: Discussionmentioning
confidence: 99%